Intellectual property and industry performance in Brazil - Silva,Marina B. (2022)
Abstract Purpose: To analyze the influence of trademark registration and patent application on the economic-financial performance of publicly traded companies in the Brazilian manufacturing industry between 1995 and 2014. Originality/value: The approach offers critical reflections for decision making by firm management and its investors. Analyses of companies’ economic and financial performance in the Brazilian manufacturing industry, based on the strategy of protecting their intellectual property, especially considering the time interval analyzed, have not been identified in recent literature. Design/methodology/approach: Manufacturing companies listed on the Brazilian stock exchange were studied. Between1995 and 2014 were considered in a sample composed of 49 companies and 746 observations. Estimates were made using panel regression models. The dependent variables are market value and return on assets. The independent variables (controlled) are trademark registrations and patent applications (intellectual property). Findings: A positive and statistically significant relationship was observed between trademark registrations and patent applications and the firms’ market value. As they are assets that reflect the company’s image in the market, the protection of trademarks seems to reflect well on the perception of the company’s shareholders, which impacts the market value. In the case of patents, the positive effect on market performance is related to the investor’s positive expectation of the firm’s application in technology, innovation, and intellectual property. No positive impact of intellectual property on the return on assets has been identified.